Nitrogen fertilization on the agro-economic performance of sesame in the Brazilian semiarid - Santos, Manoel Galdino dos; Souza, Ênio Gomes Flôr; Souza, Leonardo Vieira de; Pereira, Luiz Aurelio Freitas; Souza, Almir Rogerio Evangelista de; Barros Júnior, Aurélio Paes; Bezerra Neto, Francisco; Silveira, Lindomar Maria da (Pesquisa Agropecuaria Brasileira, 2021)
The objective of this work was to evaluate the agro-economic performance of sesame (Sesamum indicum) under nitrogen fertigation in the semiarid region of Northeastern Brazil. The experimental design was randomized complete blocks with four replicates, and the treatments were arranged in a split-plot, where the plots were assigned five N rates (0, 30, 60, 90, and 120 kg ha-1) and the sub-plots were represented by four sesame genotypes ('CNPA G2', 'CNPA G3', 'CNPA G4', and 'BRS Seda'). The following variables were evaluated in two agricultural harvests in 2016: gross and net incomes, rate of return, and profit margin. In both harvests, there was a variation in production costs between N rates. In the second harvest, the highest values of net income were achieved with 120 kg ha-1 N fertigation, being: R$7,428.36 ha-1 for 'CNPA G2', R$8,630.74 ha-1 for 'CNPA G3', R$9,828.64 ha-1 for 'CNPA G4', and R$8,354.06 ha-1 for 'BRS Seda'. Increasing N rates provide an increase in the gross income, net income, rate of return, and profit margin for sesame producers. Fertigation with 120 kg ha-1 N provides the maximum agro-economic performance for sesame, whereas the 'CNPA G4' genotype shows the greatest agro-economic efficiency.